Method for preparing mesoporous material by using sewer sludge and application thereof

CN122999130APending Publication Date: 2026-10-30CHINA THREE GORGES CORPORATION +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611255292.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但发明人研究发现重金属并非一定要进行去除,且中高浓度的酸液处理会使得原料中的重金属大量浸出,浸出液还需要另行处理

Benefits of technology

本发明以通沟污泥为原料,其硅铝含量高且有机质含量低,适合作为介孔材料的前体。由于通沟污泥中的钙铁杂质存在,会干扰后续的晶化步骤。具体地,钙在碱熔-水热体系中会优先与硅酸根结合生成化学惰性的硅酸钙(CaSiO3)或方钠石杂晶,不仅大量消耗体系中可利用的活性硅源,导致沸石产率下降,还可能附着于沸石晶核表面阻碍其进一步生长;铁则倾向于以Fe³+形式进入沸石骨架或占据孔道,虽然适量掺杂可产生缺陷位点,但过量铁(Fe2O3>5%)会严重降低沸石结晶度,使产品的孔道结构塌陷、比表面积锐减;发明人通过酸浸处理能够有效去除通沟污泥中的钙和铁,提升材料的吸附性能。发明人还意外发现,如果采用低浓度的酸液处理,其重金属析出较少,制得介孔材料的吸附效果较佳,而采用高浓度的酸液进行处理后,酸液中重金属浸出增加,介孔材料的吸附性能反而下降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to solid waste treatment technical field, disclose a kind of method for preparing mesoporous material using ditching sludge and its application, when the mesoporous material is prepared, first, ditching sludge is added to dilute acid and heated to mix, wash to neutral, dry and mix with solid sodium hydroxide and grind, calcine in air atmosphere, after calcining, cooling;Again, the obtained material is added to water, and the gel is formed by stirring and aging at room temperature, hydrothermal crystallization is carried out, and finally, washing and drying are carried out to obtain mesoporous material.The material has good adsorption performance and can be used as an adsorbent, especially suitable for removing phosphate and / or arsenate from water as an adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste treatment technology, specifically to a method for preparing mesoporous materials using sewage sludge from drainage ditches and its application. Background Technology

[0002] Sewage sludge is a solid waste generated during the long-term operation of urban drainage networks from the continuous deposition and dredging of suspended particulate matter carried by rainwater runoff, domestic sewage, and industrial wastewater. Its composition is complex, containing silica-alumina minerals such as sand and clay, as well as some decaying organic matter and microbial residues. Crucially, it is also enriched with heavy metals such as Pb, Zn, and Cu. Currently, the mainstream disposal method for sewage sludge is still sanitary landfill after dewatering. This extensive approach not only occupies a large amount of land resources and incurs high construction and maintenance costs for landfills, but also faces long-term environmental risks. Under acidic rainfall or microbial action, unstable heavy metals in the sludge can continuously leach out, posing a potential threat to surrounding soil and groundwater. Therefore, how to safely, thoroughly, and economically recycle sewage sludge has become a pressing technical challenge in the municipal environmental protection field.

[0003] Converting sewage sludge into zeolite-based adsorbents is a promising approach, as it fully utilizes the siliceous and aluminous minerals inherent in the sludge. The classic alkaline fusion-hydrothermal synthesis method involves first calcining the sludge at high temperatures to activate the siliceous and aluminous components, then inducing crystallization into zeolite under hydrothermal conditions. However, to obtain zeolites with specific crystal forms (such as type A and type X) and high crystallinity, the molar ratio of silicon to aluminum in the reaction system must be precisely controlled. Due to the high uncertainty in sludge composition, additional commercial silicon or aluminum sources are usually required for ratio adjustment, increasing costs. Furthermore, the inventors have discovered that existing technologies consider heavy metals (Pb, Zn, Cu, etc.) in the sludge as harmful interfering impurities in zeolite synthesis, as they may form independent hydroxide or oxide impurities during crystallization, hindering the formation and growth of zeolite nuclei and even leading to excessive leaching toxicity in the product. Therefore, a common practice is to leach the sludge with high-concentration inorganic acids for an extended period to dissolve and transfer all heavy metals to the liquid phase. The leachate is then treated to render it harmless through sulfide precipitation or chelating resin adsorption, while the solid phase is used for the preparation of subsequent adsorption materials. This method requires large amounts of acid and alkali solutions and generates secondary hazardous waste containing heavy metals. Essentially, it only transfers pollution between phases and fails to achieve a complete cure.

[0004] CN117125957 A discloses a method for preparing ceramic adsorbent materials by sintering a mixture of sewage sludge from sewer trenches and red mud. The method involves first mixing red mud and sewage sludge, then adding a 3 mol / L hydrochloric acid solution for modification, followed by drying using a filter. The mixture is then ball-milled into powder, and bentonite, fly ash, and a binder are added to form granular material. Finally, the granular material is sintered to obtain the ceramic adsorbent material. Its specific surface area reaches 67.3 m². 2 The ceramic adsorbent material achieves a removal rate of over 97% for six heavy metals: Cd, Pb, Cr, Cu, Zn, and Ni. During its preparation, red mud and sewage sludge are acid-modified. The acid-washed solid waste materials contain a large number of activated metal ions, which are then fixed onto the pores and structural framework of the ceramic material, resulting in excellent heavy metal adsorption. This material can be used to adsorb and treat wastewater containing excessive heavy metals, effectively reducing the heavy metal content in the wastewater. However, the inventors discovered that heavy metals do not necessarily need to be removed, and high-concentration acid treatment can cause a large amount of heavy metals to leach from the raw materials, requiring further treatment of the leachate. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a method for preparing mesoporous materials using sewage sludge and its application. The method involves heat treatment with a low concentration of acid to effectively remove calcium and iron impurities from the sludge, while retaining heavy metals in the sludge without specifically removing them. After the mesoporous material is prepared, the presence of heavy metals allows the material to act as an adsorbent to remove phosphates and / or arsenates from the water.

[0006] The technical solution of the present invention is a method for preparing mesoporous materials using sewage sludge from drainage ditches, comprising the following steps: S1. Add the sludge from the drainage ditch to dilute acid, mix, heat and react to separate the solid and liquid, wash with water until neutral, and dry for later use. The sludge obtained from S2 and S1 is mixed with solid sodium hydroxide and ground. It is then calcined in air at a temperature of 500-600℃ for 1-2 hours and then cooled for later use. The materials obtained from S3 and S2 are added to water at a solid-liquid ratio of 1:6~15, stirred and aged at room temperature to form a gel, then subjected to hydrothermal crystallization, and finally washed and dried to obtain a mesoporous material.

[0007] Furthermore, by weight percentage, the sludge in the drainage ditch contains SiO2, Al2O3, CaO, and Fe2O3; the organic matter content is less than 20%; it also contains one or more of the heavy metals Pb, Zn, or Cu; and the water content is controlled below 70%.

[0008] Furthermore, the dilute acid in S1 is dilute hydrochloric acid or dilute nitric acid, with a concentration of 0.3~1.2 mol / L.

[0009] Furthermore, the amount of dilute acid added is 2 to 4 times the mass of the sludge in the drainage ditch.

[0010] Furthermore, the heating reaction temperature in S1 is 65~75℃, and the stirring time is 1~2 hours.

[0011] Furthermore, the mass ratio of sludge to sodium hydroxide in S2 is 1:1.2~1.5.

[0012] Furthermore, the room temperature stirring aging time in S3 is 8~15h; the hydrothermal crystallization temperature is 95~100℃, and the crystallization time is 20~28h.

[0013] The present invention also relates to mesoporous materials prepared by the method.

[0014] The present invention also relates to the application of the mesoporous material prepared by the method or the mesoporous material of claim 8 as an adsorbent.

[0015] Furthermore, the adsorbent is used to remove phosphates and / or arsenates from water.

[0016] The present invention has the following beneficial effects: This invention uses sewage sludge from drainage ditches as raw material. Its high silica and aluminum content and low organic matter content make it suitable as a precursor for mesoporous materials. However, the presence of calcium and iron impurities in the sludge interferes with subsequent crystallization steps. Specifically, in the alkali-fusion-hydrothermal system, calcium preferentially combines with silicate ions to form chemically inert calcium silicate (CaSiO3) or sodalite impurities. This not only consumes a large amount of available active silicon source in the system, leading to a decrease in zeolite yield, but may also adhere to the surface of zeolite crystal nuclei, hindering their further growth. Iron, on the other hand, tends to combine with Fe³⁺. + While moderate doping can create defect sites by incorporating iron into the zeolite framework or occupying pores, excessive iron (Fe2O3 > 5%) severely reduces zeolite crystallinity, causing the pore structure of the product to collapse and the specific surface area to decrease sharply. The inventors found that acid leaching effectively removes calcium and iron from sewage sludge, improving the material's adsorption performance. They also unexpectedly discovered that low-concentration acid treatment results in less heavy metal leaching and better adsorption performance of the mesoporous material, while high-concentration acid treatment increases heavy metal leaching, leading to a decrease in the adsorption performance of the mesoporous material.

[0017] This invention employs dilute acid treatment of sewage sludge, causing partial dealuminization / desiliconization of the amorphous aluminosilicates and clay minerals in the sludge, forming an active gel layer rich in Si-OH / Al-OH. During the acid washing process, heavy metals are not fully dissolved and remain within the material. In the subsequent alkali fusion treatment, air-atmosphere calcination is performed, depolymerizing the aluminosilicate minerals into soluble precursors. Simultaneously, the residual organic matter in the sludge is oxidized and burned off, exposing more active interfaces and avoiding the physical obstruction of zeolite crystallization by residual carbon. During the gelation and hydrothermal crystallization stages, a zeolite framework is formed. Heavy metals enter the zeolite framework and undergo isomorphous substitution, forming framework-doped permanent charge defects. Some exist outside the zeolite framework in the form of highly dispersed amorphous hydroxides or oxides, firmly anchored to the surface or pores of zeolite grains through MO-Si bonding, serving as charge compensation sites. The leaching rate of this chemically bonded species is extremely low under normal operating conditions (pH 4~10).

[0018] The sludge from the drainage ditch of this invention, after being treated with dilute acid and alkali calcination, forms a rich mesoporous structure, which can be used as an adsorbent. At the same time, the retention of heavy metals during the treatment process endows the material with excellent adsorption performance for anionic pollutants, making it particularly suitable for the effective removal of phosphates and / or arsenates from water bodies. Detailed Implementation

[0019] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, all raw materials and reagents used are commercially available.

[0020] The method for preparing mesoporous materials using sewage sludge provided by this invention includes the following steps: S1. Add the sludge from the drainage ditch to dilute acid, mix, heat and react to separate the solid and liquid, wash with water until neutral, and dry for later use. The sludge obtained from S2 and S1 is mixed with solid sodium hydroxide and ground. It is then calcined in air at a temperature of 500-600℃ for 1-2 hours and then cooled for later use. The materials obtained from S3 and S2 are added to water at a solid-liquid ratio of 1:6~15, stirred and aged at room temperature to form a gel, then subjected to hydrothermal crystallization, and finally washed and dried to obtain a mesoporous material prepared by self-doping of endogenous heavy metals from sludge in drainage ditches.

[0021] In the preferred embodiment, the sludge used for draining the ditch contains SiO2, Al2O3, CaO, Fe2O3 and organic matter by weight percentage; it also contains one or more of the heavy metals Pb, Zn or Cu; and the water content is controlled below 70%.

[0022] In some embodiments, the dilute acid in S1 is dilute hydrochloric acid or dilute nitric acid; dilute hydrochloric acid is preferred. The concentration of the dilute acid is 0.3~1.2 mol / L, including but not limited to 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, or 1.2 mol / L. Preferably, it is 0.5 mol / L to 1.2 mol / L, more preferably 0.5 mol / L.

[0023] In some embodiments, the amount of dilute acid added is 2 to 4 times the mass of the sludge used for dredging. This includes, but is not limited to, 2 times, 3 times, 3.5 times, or 4 times; preferably 3 times.

[0024] In some embodiments, the heating reaction temperature in S1 is 65~75°C, and the stirring time is 1~2 hours. Preferably, the reaction temperature is 70°C, and the reaction time is 2 hours.

[0025] In some embodiments, the mass ratio of sludge to sodium hydroxide in S2 is 1:1.2~1.5. Preferably, the mass ratio of sludge to sodium hydroxide is 1:1.3.

[0026] In some embodiments, the room temperature stirring and aging time in S3 is 8 to 15 hours; including but not limited to 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, preferably 12 hours.

[0027] In some embodiments, the hydrothermal crystallization temperature is 95~100°C, and the crystallization time is 20~28 hours. More preferably, the crystallization time is 24 hours.

[0028] The sludge treated by the above method can form a mesoporous structure after dilute acid treatment and alkali calcination, and can ultimately be used to prepare mesoporous materials.

[0029] Studies have found that this mesoporous material can be used as an adsorbent. In particular, it exhibits excellent adsorption performance when used as an adsorbent to remove phosphates and / or arsenates from water.

[0030] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention.

[0031] The sludge used in the following examples and comparative examples was sourced from the drainage network of a certain city. On a dry basis by weight percentage, the main components were SiO2 42.5%, Al2O3 15.8%, CaO 8.2%, Fe2O3 6.7%, and organic matter 12.3%; the heavy metal content was: Pb 320 mg / kg, Zn 850 mg / kg, and Cu 180 mg / kg.

[0032] Example 1 Method for preparing mesoporous materials using sewage sludge from drainage ditches (1) Acid treatment: Take 100 g of ditch sludge with a moisture content of about 60% after dehydration, put it into 300 mL of dilute hydrochloric acid with a concentration of 0.5 mol / L, and stir and wash for 2 hours in a constant temperature water bath at 70℃. Separate by hot filtration, and repeatedly rinse the solid phase with deionized water until the pH of the filtrate is close to neutral. Dry at 105℃ to constant weight to obtain about 74 g of acid-washed sludge.

[0033] After acid washing, most of the heavy metals such as Pb, Zn, and Cu in the sludge remained in the solid phase, while the CaO content decreased to 1.3% and Fe2O3 to 2.1%, indicating that interfering ions were effectively removed. During the acid treatment process, Ca²⁺ can be effectively dissolved. + Fe³ + Interfering ions. During the rinsing process, as the pH of the system gradually rises from acidic, these ions are dispersed again as amorphous hydroxides on the surface and within the pores of the sludge particles, and then enter subsequent processes.

[0034] (2) Alkali fusion roasting: Weigh 20 g of the above-mentioned pickled sludge, add 26 g of solid sodium hydroxide (alkali-sludge mass ratio 1:1.3), and grind and mix evenly in a mortar.

[0035] The mixture was then transferred to a nickel crucible, placed in a muffle furnace, heated to 600°C at 10°C / min, and calcined at a constant temperature for 2 hours. After natural cooling to room temperature, a light green alkali-fused clinker was obtained.

[0036] (3) Hydrothermal crystallization: Transfer all the obtained alkali-fused clinker into a 500 mL polytetrafluoroethylene beaker, add deionized water at a solid-liquid ratio of 1:10, and stir continuously at room temperature for 12 hours to form a uniform gel.

[0037] The gel was transferred into a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, sealed, and statically crystallized in a 95°C oven for 24 hours.

[0038] After the crystallization reaction is completed, the mixture is cooled, filtered, and repeatedly washed with deionized water until the pH of the filtrate is neutral. The filtrate is then dried at 105°C for 12 hours to obtain the mesoporous material.

[0039] Example 2 Method for preparing mesoporous materials using sewage sludge from drainage ditches (1) Acid treatment: Take 100 g of ditch sludge with a moisture content of about 60% after dehydration, put it into 300 mL of dilute hydrochloric acid with a concentration of 0.3 mol / L, and stir and wash for 2 hours in a constant temperature water bath at 70℃. Separate by hot filtration, and repeatedly rinse the solid phase with deionized water until the pH of the filtrate is close to neutral. Dry at 105℃ to constant weight to obtain about 76 g of acid-washed sludge.

[0040] (2) Alkali fusion roasting: Weigh 20 g of the above-mentioned pickled sludge, add 24 g of solid sodium hydroxide (alkali-sludge mass ratio 1:1.2), and grind and mix evenly in a mortar.

[0041] The mixture was then transferred to a nickel crucible, placed in a muffle furnace, heated to 550°C at 10°C / min, and calcined at a constant temperature for 2 hours. After natural cooling to room temperature, a light green alkali-fused clinker was obtained.

[0042] (3) Hydrothermal crystallization: Transfer all the obtained alkali-fused clinker into a 500 mL polytetrafluoroethylene beaker, add deionized water at a solid-liquid ratio of 1:10, and stir continuously at room temperature for 12 hours to form a uniform gel.

[0043] The gel was transferred into a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, sealed, and statically crystallized in a 90°C oven for 36 hours.

[0044] After the crystallization reaction is completed, the mixture is cooled, filtered, and repeatedly washed with deionized water until the pH of the filtrate is neutral. The filtrate is then dried at 100°C for 12 hours to obtain the mesoporous material.

[0045] Example 3 Method for preparing mesoporous materials using sewage sludge from drainage ditches (1) Acid treatment: Take 100 g of ditch sludge with a moisture content of about 60% after dehydration, put it into 300 mL of dilute hydrochloric acid with a concentration of 1.2 mol / L, and stir and wash for 2 hours in a constant temperature water bath at 70℃. Separate by hot filtration, and repeatedly rinse the solid phase with deionized water until the pH of the filtrate is close to neutral. Dry at 105℃ to constant weight to obtain about 73 g of acid-washed sludge.

[0046] (2) Alkali fusion roasting: Weigh 20 g of the above-mentioned pickled sludge, add 36 g of solid sodium hydroxide (alkali-sludge mass ratio 1:1.8), and grind and mix evenly in a mortar.

[0047] The mixture was then transferred to a nickel crucible, placed in a muffle furnace, heated to 600°C at 10°C / min, and calcined at a constant temperature for 2 hours. After natural cooling to room temperature, a light green alkali-fused clinker was obtained.

[0048] (3) Hydrothermal crystallization: Transfer all the obtained alkali-fused clinker into a 500 mL polytetrafluoroethylene beaker, add deionized water at a solid-liquid ratio of 1:10, and stir continuously at room temperature for 12 hours to form a uniform gel.

[0049] The gel was transferred into a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, sealed, and statically crystallized in a 100°C oven for 12 hours.

[0050] After the crystallization reaction is completed, the mixture is cooled, filtered, and repeatedly washed with deionized water until the pH of the filtrate is neutral. The filtrate is then dried at 105°C for 12 hours to obtain the mesoporous material.

[0051] Comparative Example 1 A method for preparing mesoporous materials using sewage sludge from drainage ditches. The raw materials are the same as in Example 1. Take 20 g of ditch sludge with a moisture content of about 60% after dehydration and set aside without acid treatment.

[0052] (1) Alkali fusion roasting: Weigh 20 g of the above sludge, add 26 g of solid sodium hydroxide (alkali-sludge mass ratio 1:1.3), and grind and mix evenly in a mortar.

[0053] The mixture was then transferred to a nickel crucible, placed in a muffle furnace, heated to 600°C at 10°C / min, and calcined at a constant temperature for 2 hours. After natural cooling to room temperature, a light green alkali-fused clinker was obtained.

[0054] (2) Hydrothermal crystallization: Transfer all the obtained alkali-fused clinker into a 500 mL polytetrafluoroethylene beaker, add deionized water at a solid-liquid ratio of 1:10, and stir continuously at room temperature for 12 hours to form a uniform gel.

[0055] The gel was transferred into a stainless steel hydrothermal reactor with a polytetrafluoroethylene liner, sealed, and statically crystallized in a 95°C oven for 24 hours.

[0056] After the crystallization reaction is completed, the mixture is cooled, filtered, and repeatedly washed with deionized water until the pH of the filtrate is neutral. The filtrate is then dried at 105°C for 12 hours to obtain the mesoporous material.

[0057] Comparative Example 2 Method for preparing mesoporous materials using sewage sludge from drainage ditches (1) Acid treatment: Take 100 g of ditch sludge with a moisture content of about 60% after dehydration, put it into 300 mL of dilute hydrochloric acid with a concentration of 1.5 mol / L, and stir and wash for 2 hours in a constant temperature water bath at 70℃. Separate by hot filtration, and repeatedly rinse the solid phase with deionized water until the pH of the filtrate is close to neutral. Dry at 105℃ to constant weight to obtain about 72 g of acid-washed sludge.

[0058] (2) Alkali fusion roasting: Weigh 20 g of the above-mentioned pickled sludge, add 26 g of solid sodium hydroxide (alkali-sludge mass ratio 1:1.3), and grind and mix evenly in a mortar.

[0059] The mixture was then transferred to a nickel crucible, placed in a muffle furnace, heated to 600°C at 10°C / min, and calcined at a constant temperature for 2 hours. After natural cooling to room temperature, a light green alkali-fused clinker was obtained.

[0060] (3) Hydrothermal crystallization: Transfer all the obtained alkali-fused clinker into a 500 mL polytetrafluoroethylene beaker, add deionized water at a solid-liquid ratio of 1:10, and stir continuously at room temperature for 12 hours to form a uniform gel.

[0061] The gel was transferred into a stainless steel hydrothermal reactor lined with polytetrafluoroethylene (PTFE), sealed, and statically crystallized in an oven at 95°C for 24 hours. After the crystallization reaction was completed, the mixture was cooled, filtered, and repeatedly washed with deionized water until the pH of the filtrate was neutral. The filtrate was then dried at 105°C for 12 hours to obtain the mesoporous material.

[0062] Comparative Example 3 Method for preparing mesoporous materials using sewage sludge from drainage ditches (1) Acid treatment: Take 100 g of ditch sludge with a moisture content of about 60% after dehydration, put it into 300 mL of dilute hydrochloric acid with a concentration of 3 mol / L, and stir and wash for 2 hours in a constant temperature water bath at 70℃. Separate by hot filtration, and repeatedly rinse the solid phase with deionized water until the pH of the filtrate is close to neutral. Dry at 105℃ to constant weight to obtain about 70 g of acid-washed sludge.

[0063] (2) Alkali fusion roasting: Weigh 20 g of the above-mentioned pickled sludge, add 26 g of solid sodium hydroxide (alkali-sludge mass ratio 1:1.3), and grind and mix evenly in a mortar.

[0064] The mixture was then transferred to a nickel crucible, placed in a muffle furnace, heated to 600°C at 10°C / min, and calcined at a constant temperature for 2 hours. After natural cooling to room temperature, a light green alkali-fused clinker was obtained.

[0065] (3) Hydrothermal crystallization: Transfer all the obtained alkali-fused clinker into a 500 mL polytetrafluoroethylene beaker, add deionized water at a solid-liquid ratio of 1:10, and stir continuously at room temperature for 12 hours to form a uniform gel.

[0066] The gel was transferred into a stainless steel hydrothermal reactor lined with polytetrafluoroethylene (PTFE), sealed, and statically crystallized in an oven at 95°C for 24 hours. After the crystallization reaction was completed, the mixture was cooled, filtered, and repeatedly washed with deionized water until the pH of the filtrate was neutral. The filtrate was then dried at 105°C for 12 hours to obtain the mesoporous material.

[0067] The heavy metal content in the acid solution after solid-liquid separation in Examples 1, 2, and 3 was detected. The detection method was in accordance with "HJ 776-2015 Determination of 32 Elements in Water by Inductively Coupled Plasma Atomic Emission Spectrometry". The results of Pb, Zn, and Cu content are shown in Table 1 below.

[0068] Table 1. Heavy metal content in the acid solution after solid-liquid separation following acid treatment in Examples 1, 2, and 3.

[0069] As can be seen from the table above, after acid treatment with hydrochloric acid of different concentrations in Examples 1, 2, and 3, the contents of Pb, Zn, and Cu in the acid solution after solid-liquid separation are significantly different. When the concentration is 1.5 mol / L, a large amount of heavy metals will dissolve, while the dissolution of heavy metals is very limited when treated with dilute acid of lower concentration.

[0070] The pore structure of the mesoporous materials obtained in Examples 1-3 and Comparative Examples 1-3 was analyzed using the nitrogen adsorption-desorption (BET) method, and the results are shown in Table 2.

[0071] Table 2. Pore structure parameters of samples obtained from different embodiments and comparative examples.

[0072] As shown in Table 2, the BET specific surface areas of Examples 1-3 are all greater than 130 m² / g, and the average pore size is in the range of 5-7 nm, which is consistent with the typical characteristics of mesoporous materials (IUPAC defines mesoporous pore size as 2-50 nm). In contrast, the specific surface area of ​​Comparative Example 1 (unwashed) is only 68.5 m² / g, indicating that acid washing pretreatment has a significant promoting effect on pore formation. The specific surface areas of Comparative Examples 2 and 3 further decreased to 52.8 and 48.3 m² / g, respectively, indicating that deep acid washing leads to the loss of skeletal aluminum and a decrease in zeolite crystallinity, resulting in a decrease in specific surface area. This is positively correlated with their lower phosphorus adsorption capacities (15.6 and 13.5 mg / g) shown in Table 3.

[0073] A potassium dihydrogen phosphate solution with an initial phosphorus concentration of 50 mg / L (calculated as P) was prepared, and 0.5 g / L of the mesoporous material samples from Examples 1-3 and Comparative Examples 1-3 were added respectively. The samples were then shaken at 25°C for 24 hours, and the remaining phosphorus concentration was measured. The specific results are shown in Table 3 below.

[0074] Table 3. Comparison of adsorption effects of samples obtained from different embodiments and comparative examples.

[0075] As can be seen from Table 3, the mesoporous materials prepared in Examples 1 to 3 have a good adsorption effect on phosphate, while the adsorption capacity of the mesoporous materials in Comparative Examples 1 to 3 decreased significantly; it can be seen that low-concentration acid treatment has a significant effect on improving the adsorption effect of phosphate by sludge in drainage ditches.

[0076] Security test The above products were subjected to leaching toxicity tests according to the methods specified in the "Identification Standard for Hazardous Waste - Leaching Toxicity Identification" (GB 5085.3-2007). See Table 4 below for details.

[0077] Table 4. Leaching toxicity tests of samples obtained from different embodiments and comparative examples.

[0078] As can be seen from the table above, the leaching concentrations of Pb, Zn, and Cu in the examples and comparative examples are all far below the national standard limits, which proves the high stability of heavy metals in materials.

[0079] The above embodiments describe preferred embodiments of the present invention, but the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other way. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention. Therefore, the protection scope of this patent should be determined by the appended claims.

Claims

1. A method for preparing mesoporous materials using sewage sludge from drainage ditches, characterized in that, Includes the following steps: S1. Add the sludge from the drainage ditch to dilute acid, mix, heat and react to separate the solid and liquid, wash with water until neutral, and dry for later use. The sludge obtained from S2 and S1 is mixed with solid sodium hydroxide and ground. It is then calcined in air at a temperature of 500-600℃ for 1-2 hours and then cooled for later use. The materials obtained from S3 and S2 are added to water at a solid-liquid ratio of 1:6~15, stirred and aged at room temperature to form a gel, then subjected to hydrothermal crystallization, and finally washed and dried to obtain a mesoporous material.

2. The method according to claim 1, characterized in that: By weight percentage, the sludge from the drainage ditch contains SiO2, Al2O3, CaO, and Fe2O3; the organic matter content is less than 20%; it also contains one or more of the heavy metals Pb, Zn, or Cu; and the water content is controlled below 70%.

3. The method according to claim 1 or 2, characterized in that: The dilute acid in S1 is dilute hydrochloric acid or dilute nitric acid, with a concentration of 0.3~1.2 mol / L.

4. The method according to claim 1, characterized in that: The amount of dilute acid added is 2 to 4 times the mass of the sludge in the drainage ditch.

5. The method according to claim 1, characterized in that: The heating reaction temperature in S1 is 65~75℃, and the stirring time is 1~2 hours.

6. The method according to claim 1, characterized in that: The mass ratio of sludge to sodium hydroxide in S2 is 1:1.2~1.

5.

7. The method according to claim 1, characterized in that: The aging time at room temperature in S3 is 8~15h; the temperature for hydrothermal crystallization is 95~100℃, and the crystallization time is 20~28h.

8. The mesoporous material prepared by the method according to any one of claims 1 to 7.

9. The application of the mesoporous material prepared by the method according to any one of claims 1 to 7 or the mesoporous material according to claim 8 as an adsorbent.

10. The application according to claim 9, characterized in that: This adsorbent is used to remove phosphates and / or arsenates from water.

Citation Information

Patent Citations

  • Method for preparing ceramic adsorption material by mixing and sintering pipe ditch sludge and red mud

    CN117125957A